Reducing GWAS Complexity. Issue 1 (2nd January 2016) - Hazelett, Dennis J.; Conti, David V.; Han, Ying; Al Olama, Ali Amin; Easton, Doug; Eeles, Rosalind A.; Kote-Jarai, Zsofia; Haiman, Christopher A.; Coetzee, Gerhard A.
ABSTRACT: Genome-wide association studies (GWAS) have revealed numerous genomic 'hits' associated with complex phenotypes. In most cases these hits, along with surrogate genetic variation as measure by numerous single nucleotide polymorphisms (SNPs) that are in linkage disequilibrium, are not in coding genes making assignment of functionality or causality intractable. Here we propose that fine-mapping along with the matching of risk SNPs at chromatin biofeatures lessen this complexity by reducing the number of candidate functional/causal SNPs. For example, we show here that only on average 2 SNPs per prostate cancer risk locus are likely candidates for functionality/causality; we further propose that this manageable number should be taken forward in mechanistic studies. The candidate SNPs can be looked up for each prostate cancer risk region in 2 recent publications in 2015 1, 2 from our groups.